Assessment of Pulmonary Aspiration among Intensive Care Patients Having Enteral Feeding by Using Nasogastric Tube - ليلى سماهر (Latakia University Journal -Medical Sciences Series, 2023)
Enteral feeding is preferred route of nutrition support in critically ill adults when GIT function is good. Enteral nutrition is recommended method to be used when oral feeding fails, so the nutrition is delivered through a tube inserted into the stomach. Enteral nutrition has some complications; Mechanical complications are represented by pulmonary aspiration. Pulmonary aspiration is defined as inhalation of the contents of the mouth, pharynx or stomach into the respiratory tract. So it’s important to evaluate pulmonary aspiration occurrence, this may help in prevention care. This study aimed to evaluate pulmonary aspiration among critically ill patients who have Enteral feeding by using nasogastric tube. Descriptive study was performed using convenience sample of (n=15) patients at intensive care unit in tishreen university hospital in lattakia, Syria. Data were collected during the period of 16/2 to 16/5 2022. A structured questionnaire used in the study was developed by researcher, this tool was tested for reliability and validity, a pilot study was done for 3 nurses to test the tool applicability. This study results show the presence blue colure (which added to feeding meal) in the aspirated secretion in the first day at the third suction trial. This study recommended applying an evidenced based practice written protocol about enteral feeding in ICU, to decrease the incidence of pulmonary aspiration.